Ältere Arbeitslose am Scheideweg zwischen Erwerbsleben und Ruhestand: Gründe für ihren Rückzug vom Arbeitsmarkt - Christina Wübbeke (Journal for Labour Market Research, 2013)
– In Germany, older unemployed people aged 58 or more years have been exempt from a fundamental principle of activating labour market policy until 2007: They have been entitled to unemployment benefit payments until taking up retirement pension without having to seek new employment (Section 428 of Social Code III). In light of the political goal of an increased labour market participation of older workers this paper deals with the reasons why the majority of older long-term unemployed people left the labour force by making use of the Facilitated Receipt of Benefits (FRB). Surveying the labour-market behaviour of this group against the background of the FRB diminishes a common methodological problem: unemployed benefit payment recipients usually must be available for employment; therefore questions about their inclination to work, their readiness to compromise and their job-search behaviour will probably lead to socially desirable answers. These distortions can be expected to be less relevant with FRB payment recipients, who are legally entitled to cease seeking employment. The empirical analysis based on a survey of recipients of the Unemployment Benefit II shows that low or no propensity to work was rarely the motive for leaving the labour market; in particular, those anticipating a low retirement income actually wanted to be re-employed. The vast majority gave three reasons for the decision to retire: an inability to cope with requirements of available jobs, a lack of job opportunities, and an absence of proper support from the public employment agency. Thus the withdrawal of older long-term unemployed people into pre-retirement cannot be attributed to a utility-maximising decision in favour of leisure and against gainful employment, but is the primary result of lacking re-employment prospects particularly for women in East Germany.
Keywords: J14; J22; J26; J64; J65; J68; 330; ältere Arbeitnehmer; Arbeitslosengeld II-Empfänger; Vorruhestand - Determinanten; Arbeitswilligkeit; Arbeitsmarktchancen; Berufsausstieg; Langzeitarbeitslose; Arbeitsanforderungen; IAB-Querschnittsbefragung; sozioökonomische Faktoren; Arbeitskräfteangebot; aktivierende Arbeitsmarktpolitik; Erwerbsbeteiligung